2010
DOI: 10.1590/s1413-65382010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da epilepsia no processo de escolarização de crianças e adolescentes

Abstract: O objetivo deste trabalho foi identificar o número de crianças com epilepsia matriculadas em escolas públicas regulares e especiais de duas cidades brasileiras e verificar se variáveis associadas à epilepsia estão correlacionadas ao tipo de escola, que as crianças frequentavam. Participaram do estudo 56 crianças e adolescentes com idade entre 7 e 14 anos e utilizaram-se para a coleta de dados dois instrumentos: Formulário de identificação da criança e Classificação de Crises de Engel. Os dados obtidos foram an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…With regard to the types of epileptic seizures, a higher prevalence of generalized crisis type was found.In a study conducted 5 , it was observed that 28 children (50%) had generalized epilepsy, 26 had localized epilepsy (46.4%) and 2 (3.6%) had left undetermined whether focal or generalized epilepsy. In a long term, children with generalized epilepsy, even with good seizure control and with normal cognitive potential, presented significant risks of developing language and learning difficulties 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the types of epileptic seizures, a higher prevalence of generalized crisis type was found.In a study conducted 5 , it was observed that 28 children (50%) had generalized epilepsy, 26 had localized epilepsy (46.4%) and 2 (3.6%) had left undetermined whether focal or generalized epilepsy. In a long term, children with generalized epilepsy, even with good seizure control and with normal cognitive potential, presented significant risks of developing language and learning difficulties 18 .…”
Section: Methodsmentioning
confidence: 99%
“…In a study performed 5 , data referring to frequency of seizures, showed that 14 of the 56 children of special and regular schools (25%), had seizure control with medication, followed by 10 children (17.8%) presenting between 1-3 seizures per day and 16 children(28.5%) presented seizure frequency ranging from 4 to 11 seizures per year and 1-3 seizures per month. This divergence of results found with the researched literature in this study is probably due to the fact that many childhood epilepsies are benign and achieve remission or seizure control with proper treatment 19 .…”
Section: Methodsmentioning
confidence: 99%